Fluctuations and Movement Patterns of Race Chicken Egg Prices in Bengkulu Province - Selmi Selmi; A. Putra; N. P. Khairunnisa; P. S. Asriani (Jurnal Sain Peternakan Indonesia, 2023)
Chicken eggs are a staple food with a high enough animal protein content, but the price is quite affordable for all levels of society. This causes the consumption of chicken eggs to be relatively high compared to other animal protein sources, but currently, the amount of production and consumption by the public is not comparable; besides that, the price offered is constantly fluctuating. This study aims to determine price fluctuations and price movement patterns of broiler chicken eggs in Bengkulu Province. The data used is secondary data. The research method uses quantitative descriptive analysis. The research results show that. The risk of fluctuations in the price of broiler eggs in Bengkulu Province has a slightly higher risk for prices at the producer level when compared to prices at the consumer level. The development pattern of broiler egg prices in Bengkulu Province generally shows a positive direction. Fluctuations in the price of broiler eggs occur in specific periods. These fluctuations occur because they coincide with religious holidays such as Ramadan, Eid al-Fitr, Christmas and New Year, the influence of the Russia-Ukraine war, and economic problems due to the Covid-19 pandemic.